The Prognostic Value and Immune Infiltration of USP10 in Pan-Cancer: A Potential Therapeutic Target - Gao, Dacheng; Zhang, Zhiwen; Xu, Rui; He, Ziyang; Li, Fangyi; Hu, Yan; Chen, Hui; Lu, Jiawei; Cao, Xingguo; Liu, Yali; Xu, Zengguang (Frontiers in Oncology, 2022)
Ubiquitin-specific peptidase 10 (USP10) can sustain cellular functions and regulate cellular processes. It plays an essential role in cancer inhibition or facilitation by reversing ubiquitin-proteasome degradation. Studies have identified USP10 to be involved in tumor progression in various cancers. However, the pan-cancer expression pattern of USP10, its prognostic value, and the association between tumor immune cell infiltration and USP10 expression remain to be discussed and thus comprised the aims of the present study. Based on clinical samples and bioinformatic analyses, high USP10 expression was observed in most cancer tissues except for ovarian cancer. High USP10 expression correlated with pathological stage and node metastasis, and predicted poor patient prognosis. In addition, further analyses at the TIMER and GEPIA databases showed that USP10 is involved in the infiltration of multiple immune cells and regulated the infiltration levels of specific immune cell subpopulations, particularly in pancreatic adenocarcinoma (PAAD) and liver hepatocellular carcinoma (LIHC). Importantly, USP10 might influence survival by modulating immune infiltration in patients with PAAD and LIHC. These results identified USP10 as a potential biomarker for pan-cancer prognosis, and in certain cancers, USP10 could identify clinical prognosis linked to tumor immune infiltration.